PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA PADA KARYAWAN KPRI "PERTAGUMA" KOTA MADIUN - Devie Putri Wijayanti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This study aims to (1) To know the motivation  of employees KPRI  "Pertaguma" Madiun,   (2) To know  employee job  satisfaction  on KPRI  "Pertaguma"    Madiun,   and (3) To know  the motivation  is there  any  influence  on job  satisfaction   in employees    KPRI "Pertaguma" Madiun.  The samples in this study using a sample that is saturated  cooperative employee   is 17. Data collection  using  interviews  and questionnaires.   Data analysed use simple  linear regression  statistical  methods,  and to test whether  or not valid  instrument used regression  methods.  The results  showed  that motivation  has a positive  influence on employee job  satisfaction  on KPRI  "Pertaguma"    Madiun.  It is derived   from the value of Fisher's  exact test, whereas  the Fcount value of 64,792  Ftabel value of 4,54.  On the other hand Sig(hit) known values of 0.000  and 0.05 known  Sig(prob) value. This means that the Fvalue >= Ftabel (64.792 >= 4.54)  or Sig(hit) <= Sig(prob) (0.05 <= 0.000).   Meaning  a rejection  of H0 which  shows  that there  is an influence  of motivation   on job  satisfaction   in employees KPRI  "Pertaguma"     Madiun.  In addition  to the values  obtained  with the  t, t(test) value  is 8.049  while the value ttable 2,131.  On the other hand Sig(hit) value of 0.000  and Sig(prob) value as 0.05. This means that t >= ttable (8.049 >= 2.131) or <= Sig(hit) Sig(prob) (0.05 <= 0.000).  It means that H0    is rejected,  meaning  that motivation   has a different  effect on employee job  satisfaction on KPRI “Pertaguma” Madiun.